Evaluación genética de la raza Comarqueña. Núcleo fundacional de la Chacra Experimental Patagones - Alvarez, Juan Mauricio; Giorgetti, Hugo; Garcia Vinent, Juan Carlos; Miñon, Daniel Pedro; Rodriguez, Gustavo; Damian, Ponce (EEA Valle Inferior, INTA, 2022)
EEA Valle Inferior